A landscape‐scale assessment of the relationship between grassland functioning, community diversity, and functional traits. Issue 18 (16th August 2020) - van 't Veen, Hanneke; Chalmandrier, Loïc; Sandau, Nadine; Nobis, Michael P.; Descombes, Patrice; Psomas, Achilleas; Hautier, Yann; Pellissier, Loïc
Abstract: Livestock farmers rely on a high and stable grassland productivity for fodder production to sustain their livelihoods. Future drought events related to climate change, however, threaten grassland functionality in many regions across the globe. The introduction of sustainable grassland management could buffer these negative effects. According to the biodiversity–productivity hypothesis, productivity positively associates with local biodiversity. The biodiversity–insurance hypothesis states that higher biodiversity enhances the temporal stability of productivity. To date, these hypotheses have mostly been tested through experimental studies under restricted environmental conditions, hereby neglecting climatic variations at a landscape‐scale. Here, we provide a landscape‐scale assessment of the contribution of species richness, functional composition, temperature, and precipitation on grassland productivity. We found that the variation in grassland productivity during the growing season was best explained by functional trait composition. The community mean of plant preference for nutrients explained 24.8% of the variation in productivity and the community mean of specific leaf area explained 18.6%, while species richness explained only 2.4%. Temperature and precipitation explained an additional 22.1% of the variation in productivity. Our results indicate that functional trait composition is an important predictor of landscape‐scale grassland productivity. Abstract : We provide a landscape‐scale assessment on the relative effect of plant species richness and plant trait composition on the productivity and variance in grassland productivity under varying climatic conditions in Switzerland. We find a relatively strong effect of functional traits on grassland productivity, while species richness slightly influences productivity. The relationships between functional traits on grassland productivity found in our study indicate the importance of including functional trait variables to explain productivity on a landscape scale.